Financial development and wage income: Evidence from the global football market - Wang, Wei; Yang, Haoxi; Wang, Xi (Journal of Banking & Finance, 2023)
This study examines the empirical relation between football players’ wage income and financial development at the individual level. Using a large panel dataset of 237,631 football players from 153 countries from 2010 to 2020 and the International Monetary Fund's Financial Development Indices, we show that financial development significantly raises players’ wages. Players’ wages increase by 25.77% as the Financial Development Index rises by one standard deviation. Our main findings are robust to using subindices of financial development and instrumental variable regressions. We further point out that football players of low capability, with low wages, and who play for low-reputation clubs benefit more from financial development.